Economic of different alternative livelihood projects in Southern Municipalities of Iloilo - Besana, Nikkei Mesa. (2006)
The study aims to determine and analyze the economics of different alternative livelihood projects in southern municipalities of Iloilo, namely Tigbauan, Miag-ao and San Joaquin.
Thesis, Undergraduate, UPV Miag-ao, BS Economics
Keywords: Livelihood projects